2014
DOI: 10.1186/1471-2164-15-1145
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic differences in community acquired methicillin resistant Staphylococcus aureus USA300 and USA400 strains

Abstract: BackgroundStaphylococcus aureus is a human pathogen responsible for substantial morbidity and mortality through its ability to cause a number of human infections including bacteremia, pneumonia and soft tissue infections. Of great concern is the emergence and dissemination of methicillin–resistant Staphylococcus aureus strains (MRSA) that are resistant to nearly all β-lactams. The emergence of the USA300 MRSA genetic background among community associated S. aureus infections (CA-MRSA) in the USA was followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…One clue to this occurrence may be related to the upregulation of the entire arc operon in the MSSP isolate studied here. A similar operon has been found in other staphylococcal species, and in S. aureus, arcA (which belongs to the arc operon) encodes an arginine deaminase, which allows for enhanced survival in acidic environments (26). The upregulation of this operon may improve survival and promote biofilm formation of MSSP in acidic circumstances, such as in BHIB medium with glucose (which has a more acidic pH than BHIB medium alone or with NaCl).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…One clue to this occurrence may be related to the upregulation of the entire arc operon in the MSSP isolate studied here. A similar operon has been found in other staphylococcal species, and in S. aureus, arcA (which belongs to the arc operon) encodes an arginine deaminase, which allows for enhanced survival in acidic environments (26). The upregulation of this operon may improve survival and promote biofilm formation of MSSP in acidic circumstances, such as in BHIB medium with glucose (which has a more acidic pH than BHIB medium alone or with NaCl).…”
Section: Discussionmentioning
confidence: 64%
“…The upregulation of this operon may improve survival and promote biofilm formation of MSSP in acidic circumstances, such as in BHIB medium with glucose (which has a more acidic pH than BHIB medium alone or with NaCl). During the early emergence of community-acquired MRSA, the USA300 (ST8) lineage disseminated rapidly and was considered hypervirulent, compared with lineages like MRSA USA400 (ST1) (26). However, USA300 does not contain many more virulence genes than USA400, but it does have an alteration in the expression of regulatory genes and increased expression of certain virulence genes (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evidence suggests that this prophage is still active in USA300 strains and its genes are expressed during lung infection, where it may play a role in establishing virulence 57 . Corroborating this hypothesis, we found that the activity of the Phi-Sa3 i-modulon correlated highly with the Vim-3…”
Section: Ica Reveals Organization Of Virulence Factor Expressionmentioning
confidence: 99%